Advances in virus-like particle-based SARS-CoV-2 vaccines - Hao, Xiaoting; Yuan, Feifei; Yao, Xuan (Frontiers in Cellular and Infection Microbiology, 2024)
The Coronavirus Disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has incurred devastating human and economic losses. Vaccination remains the most effective approach for controlling the COVID-19 pandemic. Nonetheless, the sustained evolution of SARS-CoV-2 variants has provoked concerns among the scientific community regarding the development of next-generation COVID-19 vaccines. Among these, given their safety, immunogenicity, and flexibility to display varied and native epitopes, virus-like particle (VLP)-based vaccines represent one of the most promising next-generation vaccines. In this review, we summarize the advantages and characteristics of VLP platforms, strategies for antigen display, and current clinical trial progress of SARS-CoV-2 vaccines based on VLP platforms. Importantly, the experience and lessons learned from the development of SARS-CoV-2 VLP vaccines provide insights into the development of strategies based on VLP vaccines to prevent future coronavirus pandemics and other epidemics.